2014
DOI: 10.1091/mbc.e14-08-1284
|View full text |Cite
|
Sign up to set email alerts
|

Membrane tethering by the atlastin GTPase depends on GTP hydrolysis but not on forming the cross-over configuration

Abstract: The atlastin GTPase couples nucleotide hydrolysis to formation of a trans cross-over dimer to catalyze homotypic endoplasmic reticulum membrane fusion. Assays that separate tethering from fusion reveal that stable trans contact for tethering depends on GTP hydrolysis. In contrast, cross-over formation is required only for the fusion step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
77
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(87 citation statements)
references
References 21 publications
(117 reference statements)
9
77
1
Order By: Relevance
“…In addition, similar tightly "zippered" opposing membranes have been reported for fusionprimed membranes tethered by the atlastin GTP-driven fusion machinery (55). Moreover, it appears that during yeast vacuolar fusion, large extended membrane contacts form, though resolution of bilayers was not attained in that case (56).…”
Section: Discussionsupporting
confidence: 56%
“…In addition, similar tightly "zippered" opposing membranes have been reported for fusionprimed membranes tethered by the atlastin GTP-driven fusion machinery (55). Moreover, it appears that during yeast vacuolar fusion, large extended membrane contacts form, though resolution of bilayers was not attained in that case (56).…”
Section: Discussionsupporting
confidence: 56%
“…Rather, the rapid association of monomers in the GTP-bound state suggests that GTP hydrolysis most likely occurs after dimerization. It also has been suggested that tethering does not require the crossover configuration characteristic of crystal forms 1 and 3 and therefore would not involve a strong interaction among the 3HBs (25). This was based on a double mutant of ATL (P319G K320E), which was defective in generating the crossover configuration but was reported to have undiminished GTPase and tethering activity (25).…”
Section: Discussionmentioning
confidence: 99%
“…It also has been suggested that tethering does not require the crossover configuration characteristic of crystal forms 1 and 3 and therefore would not involve a strong interaction among the 3HBs (25). This was based on a double mutant of ATL (P319G K320E), which was defective in generating the crossover configuration but was reported to have undiminished GTPase and tethering activity (25). Although we agree that the mutant has GTPase activity similar to that of WT ATL, we found that it is significantly less active in tethering (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations